Photostability enhancement of InP/ZnS quantum dots enabled by In2O3 overcoating - Jo, Jung-Ho; Kim, Jong-Hoon; Lee, Sun-Hyoung; Jang, Ho Seong; Jang, Dong Seon; Lee, Ju Chul; Park, Ko Un; Choi, Yoonyoung; Ha, Chunghun; Yang, Heesun (ELSEVIER SCIENCE SA, 2015)
Although the present-level quantum dots (QDs) exhibit excellent photoluminescent performance, their photostability under a prolonged photoexcitation stays doubtful and still unsatisfactory from an industrial perspective, since it determines the reliability of QD-incorporated devices such as QD-lightemitting diodes (QD-LEDs). In the present work, the overcoating of red-emitting InP/ZnS QDs with the oxide phase of In2O3 is attempted to suppress the QD photooxidation, thus rendering them highly photostable. The efficacy of the oxide overlayer in substantially alleviating the QD photodegradation is verified through a comparative photostability test, where two colloidal solutions of bare versus In2O3-overcoated InP/ZnS (InP/ZnS@ In2O3) QDs are identically subjected to a continuous UV irradiation for an extended period of time. Furthermore, both InP/ZnS and InP/ZnS@In2O3 QDs are packaged as color-converters with a blue LED chip, and the operational stability of the fabricated QD-LEDs is examined at a forward bias of 60 mA. Consistent with the results of UV irradiation experiment, InP/ZnS@ In2O3 QD-LED exhibits a superior device stability against a continual operation as compared with InP/ZnS one. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: LIGHT-EMITTING-DIODES; INP-AT-ZNSES; OPTICAL-PROPERTIES; LUMINESCENT NANOCRYSTALS; OPERATIONAL STABILITY; FACILE SYNTHESIS; SHELL THICKNESS; SILICA; EFFICIENT; CONVERTER